Adapting to water scarcity: constraints and opportunities for improving irrigation management in Khorezm, Uzbekistan - Tischbein, B.; Manschadi, A.M.; Conrad, C.; Hornidge, A.-K.; Bhaduri, Anik; Ul-Hassan, Mehmood; Lamers, John P.A.; Awan, Usman K.; Vlek, Paul L.G. (IWA Publishing, 2013)
Like many irrigation schemes in Central Asia, the one in Khorezm faces a two-fold challenge: on the one side, the severe problems inherited from the past need to be remedied and on the other side, the rising supply-demand gap driven by sharpening competition for water and climate change must be dealt with. Located in the lower part of the Amu Darya basin, Khorezm irrigation and drainage scheme is particularly vulnerable to supply-demand gaps. Promising solutions towards adaptation comprise modified strategies of land and water use towards higher efficiency and flexibility in combination with measures to lessen the constraints of the system itself, which was initially designed for the management of a few, large and uniform production units and not for many diverse and small units. Solutions consist of flexible, modeling-based approaches, re-arranging institutional settings and establishing economic incentive systems. Flexible modeling allows an integrated use of surface and groundwater resources avoiding or minimizing the impact of water stress on yield. Institutional settings strengthen the position of water users via improved participation and transparency of processes in Water Consumers Associations (WCAs). Economic measures support sustainable resource use strategies and improve the functioning of WCAs. The findings could be extrapolated to other regions of Central Asia with similar conditions and challenges.